Multi-material ceramic material extrusion 3D printing with granulated injection molding feedstocks. Issue 4 (15th February 2023) - Wick-Joliat, René; Schroffenegger, Martina; Penner, Dirk
Abstract: Material Extrusion (MEX) is an advanced technology for polymer 3D printing and countless printers are commercially available. MEX has also been demonstrated for ceramics. For that purpose, thermoplastic binders are filled with high loads (>40 vol%) of a ceramic powder. The printed parts are subsequently debound and sintered. In contrast to most MEX printers, the ceramic printer presented herein works with granulated feedstock instead of filaments. Therefore, the development of novel feedstocks is faster and more straightforward since the challenges associated with filament production are omitted. Furthermore, commercial ceramic injection molding (CIM) feedstocks can be used which allows fast prototyping with the same material that is later used in high-quantity industrial production by CIM. In this study, a method to fabricate multi-material ceramic parts using a granulate-fed printer is presented. Examples of multi-material printing include colored ZrO2 parts as well as ceramic high-temperature heating elements in various shapes consisting of an electrically conductive and a non-conductive component. Light- and electron microscopy confirms that the layer adhesion before and after sintering is flawless, even between different materials if the material combination is chosen carefully. All feedstocks are based on a commercially available CIM binder filled with the desired ceramic powder. Consequently, the feedstock preparation as well as optimizing of debinding and sintering conditions are simple and reproducible.